Reversible Redox, Spin Crossover, and Superexchange Coupling in 3d Transition‐Metal Complexes of Bis‐azinyl Analogues of 2, 2′:6′, 2′′‐Terpyridine. Issue 10 (13th March 2018) - Zhang, Yixin; Harriman, Katie L. M.; Brunet, Gabriel; Pialat, Amélie; Gabidullin, Bulat; Murugesu, Muralee
Abstract : The terpyridine‐inspired tridentate ligand, 2, 6‐bis(5, 6‐dialkyl‐1, 2, 4‐triazin‐3‐yl)‐pyridine (BTP), was synthesized and utilized to isolate five [M II (BTP)2 ] 2+ (M = Fe and Co) transition‐metal complexes of various anions (BF4 –, ClO4 –, and NCS – ). Notably, when metal‐halide precursors are employed, 1:1 M/L products [Co2 II (µ‐X)2 (BTP)2 X2 ] (X = Cl or Br) are obtained, exhibiting µ‐halide bridges. All complexes were structurally characterized through single‐crystal X‐ray diffraction and their electrochemical and magnetic properties were investigated. Electrochemical studies reveal that the free BTP ligand has a single irreversible reduction, however; upon coordination to a metal center, stabilization of the reduced BTP ligand occurs and up to four reductive processes associated with the molecule are observed within the solvent window. The metal‐centered redox processes were either reversible or partially reversible, and fall within the range of 0.13 < E1/2 < 0.90 V vs. Fc/Fc + . Although there was minimal effect on the redox properties of the metal centers, there is strong dependence on the spin state. SQUID magnetometry elucidated a low spin state for the Fe II complexes at room temperature, revealing a diamagnetic electronic structure. On the other hand, the cobalt monometallic complexes, [Co II (BTP)2 ] 2+, showed gradual spin crossover properties between 1.8–370 K, displaying a minor dependence on the spin crossover behavior based on the respective anion. Additionally, ferromagnetic exchange interactions of J = +2.57 and +2.98 cm –1 were obtained using the –2 J formalism for the dinuclear Co II complexes, [Co2 II (µ‐X)2 (BTP)2 X2 ] for X = Cl and Br, respectively. Abstract : A series of Fe/Co complexes was synthesized and isolated by 2, 6‐bis(5, 6‐dialkyl‐1, 2, 4‐triazin‐3‐yl)‐pyridine (BTP) with transition‐metal salts of various anions. The complexes were structurally characterized through single‐crystal X‐ray diffraction and their interesting electrochemical and magnetic properties were investigated.